Moesin is a possible target molecule for cytomegalovirus-related Guillain-Barré syndrome - Sawai, Setsu; Satoh, Mamoru; Mori, Masahiro; Misawa, Sonoko; Sogawa, Kazuyuki; Kazami, Takahiro; Ishibashi, Masumi; Beppu, Minako; Shibuya, Kazumoto; Ishige, Takayuki; Sekiguchi, Yukari; Noda, Kenta; et al. (Neurology, 2014)
Previous histochemical studies in the demyelinating form of Guillain-Barré syndrome (GBS), acute inflammatory demyelinating polyneuropathy (AIDP), have shown complement deposition on the surface of Schwann cells, and therefore unknown epitopes would be present on the outer surface of Schwann cells. We used a proteomic-based approach to search for the target molecules of AIDP in the extracted proteins from schwannoma cells. Sera were obtained from 40 patients with GBS, 31 controls with inflammatory disease, and 46 normal controls. We found that patients with AIDP after cytomegalovirus (CMV) infection have serum autoantibodies against membrane-organizing extension spike protein (moesin), which is expressed in the Schwann cell processes at the nodes of Ranvier and is crucial for myelination. Of the 40 patients with GBS, 6 had recent CMV infection and 5 of them (83%) had high levels of serum immunoglobulin G antibodies against moesin. The anti-moesin antibodies were found in none of the control subjects with disease including 5 with CMV infection but no neuropathy, and only 2 (4%) of the 46 normal control subjects. Immunocytochemistry showed that moesin was stained at the distal tips of schwannoma cells by sera from the patients with CMV-related AIDP but not by sera from controls. Moesin is a possible immunologic target molecule of pathogenic autoantibodies in patients with CMV-related AIDP. This study provides Class II evidence that levels of serum anti-moesin antibodies accurately distinguishes CMV-related AIDP from non-CMV-related AIDP (sensitivity 83%, specificity 93%).